Energy Absorption Evaluation of CFRP-Strengthened Two-Spans Reinforced Concrete Beams under Pure Torsion - Ammar N. Hanoon; Ali A. Abdulhameed; Haider A. Abdulhameed; Saad K. Mohaisen (Salehan Institute of Higher Education, 2019)
For more than a decade, externally bonded carbon fiber reinforced polymer (CFRP) composites successfully utilized in retrofitting reinforced concrete structural elements. The function of CFRP reinforcement in increasing the ductility of reinforced concrete (RC) beam is essential in such members. Flexural and shear behaviors, ductility, and confinement were the main studied properties that used the CFRP as a strengthening material. However, limited attention has been paid to investigate the energy absorption of torsion strengthening of concrete members, especially two-span concrete beams. Hence, the target of this work is to investigate the effectiveness of CFRP-strengthening technique with regard to energy absorption of two-span RC beams subjected to pure torsion. The experimental program comprises the investigation of two groups; the first group comprises eight un-strengthened beam specimens, while the second group consists of eight strengthened beam specimens tested under torsional forces. The energy absorption capacity measured from the area under the curve of torque-angle of twist for tested beams. Two parameters were studied, the influence of concrete compressive strength and the angle of a twist. Experimental results indicated that all beams wrapped with CFRP sheet display superior torsional energy absorption capacity compared to the control specimens. The energy absorption may consider as a safety index for the torsional capacity of two-span RC beams under service loadings. Therefore, it is possible to avoid structural as well as material damages by understanding the concept of energy absorption that is one of the important experimental findings presented in this study.